Preskušanje materialov na odpornost proti utrujanju pri kotaljenju - Kalin, Mitjan (Kovine zlitine tehnologije, 1998)
Rolling contact fatigue testers could be classified into bench and model devices. Due to rotational movement, complex contact geometry, high speeds, and high tolerances both types of devices are expensive. In this paper new own-designed RCF tester is presented. In contrast to most of today's similar devices, loading part in the new tester moves linearly reciprocatingly and rolls the ball over the flat specimen. Simple testing principle and specimens geometry make RCF testing with the new tester less expensive than with comparative devices.
Keywords: strojni elementi; utrujanje materiala; preizkušanje